Analyzing Communication Patterns in Long-Distance Parent-Child Relationships: A Mixed-Methods Study - Mantofani Andreas; Nur Hasanah (IHSA Institute, 2024)
This study investigates the communication patterns in long-distance parent-child relationships, aiming to understand the nuances of maintaining familial bonds across geographical divides. Through a mixed-methods approach, the research examines the frequency, duration, and content of communication, as well as the challenges and strategies employed by families. Data are collected through surveys, interviews, and communication logs, and analyzed using both quantitative and qualitative methods. The findings reveal a diverse array of communication patterns among parent-child dyads, ranging from daily video calls to less frequent text messages or emails. While communication frequency and duration varied widely, the qualitative data highlighted the importance of meaningful communication in fostering emotional closeness and relationship satisfaction. However, the study also uncovered several challenges, including time zone differences, technological barriers, and the emotional toll of separation. Furthermore, the study emphasizes the need for families to adapt their communication strategies to accommodate cultural and generational differences, as well as the evolving landscape of digital communication technologies. By recognizing and navigating these complexities, families can better navigate separation and maintain strong connections across distances.